Catalytic cracking of castor oil via microwave assisted method - W.J., Kh’ng; Wan Asma, Ibrahim; Zulkafli, Hassan; Izirwan, Izhab (Elsevier Ltd, 2022)
Castor oil extracted from seeds of Ricinus Communis plant has an immense potential being used to yield valuable hydrocarbons with shorter chain length. Castor oil contains chemical structures of heavy hydrocarbons and long chains may undergo a cracking process which are similar to that as in petrochemical industries. However, cracking process requires extremely high temperature and energy input. This research came by with an attempt to reduce waste of energy using both microwave assisted method and modified metal catalyst, Zn/ZSM-5 to provide sufficient energy for cracking process to occur at comparatively low temperature. Wet impregnation method was used for Zn/ZSM-5 catalyst preparation and the experiments were carried out via microwave-assisted method. The microwave effect on the temperature and mass of condensate formed was investigated at three different output powers; 650, 700 and 750 W, under different Zn/ZSM-5 concentrations; 5, 8 and 10 wt% for 1 h. Results showed that cracking of castor oil is feasible at low temperature (<250 ◦C) using modified Zn/ZSM-5 via microwave assisted method. The highest yield of total mass of condensate (5.61%) was obtained from 750 W output power and 10 wt% Zn/ZSM-5 catalyst concentration. In addition, the highest cracking percentage (97.7%) was obtained from 750 W output power and 5 wt% Zn/ZSM-5 catalyst concentration. Valuable cracked compounds such as octane for fuel products and undecylenic acid for pharmaceutical uses were obtained.